Giving Tuor At Mandailing Tribe Marriages Compilation Perspective Of Islamic Law In Mandailing Natal - Aripin, Musa; Pagar, Pagar; Marpaung, Watni (Faculty of Law, Universitas Pekalongan, 2024)
The issue of tuor (the amount of money given by the groom to the bride upon the agreement of both families) in the Mandailing tribe is interesting to be studied. This is quite reasonable because the problem of tuor, on the one hand can actually make a number of marriage plans forced to be canceled. At the same time the majority of the Mandailing tribe are devout adherents of Islam. While Islam itself has the same concept as the tuor, namely dowry. Testing tuor at the application level is something that must be done to measure the extent of the phenomenon. On the other hand, measuring tuor conceptually is also needed to provide a complete view. The results showed that the tuor and dowry in the KHI have the same substance, namely the obligatory gift from the prospective husband to the prospective wife. However, the provision of tuor has advantages, namely the philosophy used in determining tuor. Holong (compassion) and Saanak Saboru (feeling that the groom’s family has considered that the bride is their daughter and vice versa). Thus it can be stated that the determination of the amount of tuor will not burden the bridegroom, because the groom in giving tuor is motivated by affection, and at the same time the parents of the bride-to-be will also not ask for something that can burden the bridegroom